Demokrasi dalam Keluarga di Ruang Komunikasi Digital Masa Kini - Ambros Leonangung Edu; Richard A Nelwan (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
This paper background describes about democratic values such as equality, honesty, openness, freedom due to the intervention of digital technology. The basic assumption of this paper is that democracy which is known to the public is accepted and has strong roots in the family lives. Family is the first place a person gets to know democracy. Home is a space for the seeds of democracy to grow. Democracy in the family matures the democratic process in society and the state. A democraticperson in  family is a democratic cittizen in state life. The purpose of this paper is to explore democratic values in the family as a place for the development of democracy at the state level, and how the shift in democracy at the family level occurs due to the presence of digital technology which distorts communication, relationships, and the value of equality. The description in this paper comes to the conclusion that there is a good side to democracy in a family that grows above physical and emotional relationships, direct and face-to-face relationships. The facts that occur in today's families, the breakdown, estrangement, and disharmony in today's families, one of which is triggered by the lack of direct communication due to excessive entry of digital technology.Keywords: Democracy; Family; Communication; Digital Technology AbstrakTulisan ini bertolak dari kemunduran nilai-nilai demokrasi di dalam seperti kesetaraan, kejujuran, keterbukaan, kebebasan, akibat intervensi teknologi digital. Asumsi dasar tulisan ini adalah bahwa demokrasi yang dikenal publik pun diterima dan berakar kuat dalam keluarga. Keluarga adalah tempat pertama kali seorang mengenal demokrasi. Rumah adalah ruang bagi bertumbuhnya bibit-bibit demokrasi. Demokrasi dalam keluarga mematangkan proses demokrasi dalam masyarakat dan negara. Seorang yang demokratis dalam keluarga berarti demokratis dalam kehidupan negara. Tujuan penulisan ini adalah untuk mengeksplorasi nilai-nilai demokrasi dalam keluarga sebagai tempat bertumbuh-kembangnya demokrasi di tingkat negara, dan bagaimana pergeseran demokrasi pada tataran keluarga terjadi akibat kehadiran teknologi digital yang mendistorsi komunikasi, relasi, dan nilai kesetaraan. Uraian dalam tulisan ini sampai pada kesimpulan bahwa terdapat sisi baik demokrasi dalam keluarga bertumbuh di atas hubungan fisik dan emosi, hubungan langsung dan tatap muka. Fakta yang terjadi pada keluarga-keluarga masa kini, keretakan, kerenggangan, dan disharmonisasi dalam keluarga-keluarga masa kini, salah satunya dipicu oleh kurangnya komunikasi langsung akibat masuknya teknologi digital yang berlebihan.Kata Kunci: Demokrasi; Keluarga; Komunikasi; Teknologi Digital